X-ray topographic observation of dislocations in β-Ga2O3 Schottky barrier diodes and their glide and multiplication under reverse bias. (15th March 2023) - Yao, Yongzhao; Wakimoto, Daiki; Miyamoto, Hironobu; Sasaki, Kohei; Kuramata, Akito; Hirano, Keiichi; Sugawara, Yoshihiro; Ishikawa, Yukari
Abstract: We observed dislocations in β-Ga2 O3 Schottky barrier diodes (SBD) using synchrotron X-ray topography (XRT) and studied their behaviors under forward or reverse bias. Several representative dislocation types were identified by observing the dislocation lines and their Burgers vectors. After comparing the XRT images taken before and after the bias was applied, we found that the dislocations were not static but could glide and multiply under a reverse bias of −140 V for 5 min. This was frequently observed near the dislocation bundles emanating from the end of a screw-type b-axis dislocation that had a Burgers vector of b∥[010]. The glide belonged to the 〈 010 〉 {001} slip system. The glide and multiplication occurred even when the dislocations were not directly located in the SBD area being electrically stressed. It is considered that the b-axis screw dislocations acted as pathways of leakage current that was the driven force for dislocation glide and multiplication. Graphical abstract: Image, graphical abstract